Structural and Dynamics Perspectives on the Binding of Substrate and Inhibitors in Mycobacterium tuberculosis DHFR - Pimonluck Sittikornpaiboon; Pisanu Toochinda; Luckhana Lawtrakul (MDPI AG, 2017)
Dihydrofolate reductase (DHFR), an essential enzyme in the folate pathway, is a potential target for new anti-tuberculosis drugs. Fifteen crystal structures of Mycobacterium tuberculosis DHFR complexed with NADPH and various inhibitors are available in the RCSB Protein Data Bank, but none of them is a substrate binding structure. Therefore, we performed molecular dynamics simulations on ternary complexes of M. tuberculosis DHFR:NADPH with a substrate (dihydrofolate) and each of three competitive inhibitors in 2,4-diaminopyrimidine series (P1, P157, and P169), in order to gain insight into the inhibition-mechanism of DHFR in the folate pathway. The binding energy and thermodynamics values of each system were calculated by the Molecular Mechanics/Generalized Born Surface Area (MM/GBSA) method. The dynamics of the enzyme and the motion of each amino acid residue at the active site were examined. The key factors that promote the binding of P157 and P169 on M. tuberculosis DHFR (mtbDHFR) reveal opportunities for using these compounds as novel anti-tuberculosis drugs.